(untitled) (Singapore, 1996)
In the post-quantum-mechanics era, few physicists, if any, have matched Julian Schwinger in contributions to and influence on the development of physics. A deep and provocative thinker, Schwinger left his indelible mark on all areas of theoretical physics; an eloquent lecturer and immensely successful mentor, he was gentle, intensely private and known for being "modest about everything except his physics". This book is a collection of talks in memory of him by some of his contemporaries and his former students: A. Klein, F. Dyson, B. DeWitt, W. Kohn, D. Saxon, P.C. Martin, K. Johnson, S. Deser, R. Finkelstein, Y.J. Ng, H. Feshbach, L. Brown, S. Glashow, K.A. Milton and C.N. Yang. From it, one can get a glimpse of Julian Schwinger, the physicist, the teacher and the man. Altogether, this book is a must for all physicists, physics students, and others who are interested in great legends.
Keywords: Vật lý,Physics; Lịch sử,History